INFLUENCE OF ORGANIZATION FACTORS ON THE PERFORMANCE OF STATE CORPORATIONS IN KENYA - Linyiru, Dr. Bruno Mugambi; Ketyenya, Dr. Rutto Peter (International Journal of Entrepreneurship and Project Management, 2017)
Purpose: The purpose of this study was to determine the influence of organization factors on the performance of state corporations in Kenya. Methodology: The study adopted an explanatory research design. The population of the research consists of the 187 state corporations in Kenya as at 2013. The unit of analysis was the state corporation. A purposive sample of 55 commercial state corporations was included in the study. The study used primary data gathered using questionnaires. Results: Results indicated that organization factors are key determinants of firm performance for commercial state corporations in Kenya. Conclusion: Organizational factors were statistically significant in explaining firm performance of commercial state corporations. It can therefore be concluded that for any firm to have better results should manage the organizational factors and nurture conducive environment for all employees to work in.